Salter–Harris type-IV displaced distal radius fracture in a 5-year-old. Issue 2 (March 2016) - Huntley, Samuel R.; Summers, Spencer H.; Stricker, Stephen J.
Abstract : Displaced Salter–Harris type-IV fractures are rare in young children and can result in articular incongruity or premature physeal arrest. We describe a 5-year-old boy who sustained a displaced left distal radial Salter–Harris type-IV fracture. The patient had normal wrist function and physeal growth at the 3-year postoperative follow-up. Our patient is by far the youngest reported child with a displaced Salter–Harris type - IV fracture of the distal radius. Prompt anatomic reduction and fixation of a displaced distal radial Salter–Harris type-IV fracture can result in excellent short-term wrist motion with maintenance of physeal function.